(untitled) (Revista de Estudos da Linguagem, 1999)
This article aims to bring some contributions to the discussion ofthe epistemological status of French Discourse Analysis. Becausethere isn’t a single answer to this question yet, this work will studyseveral authors and their observations about the French DiscourseAnalysis and its epistemologicals limits.